BODIPY as electron withdrawing group for the activation of double bonds in asymmetric cycloaddition reactions. Issue 15 (20th March 2019) - Guerrero-Corella, Andrea; Asenjo-Pascual, Juan; Pawar, Tushar Janardan; Díaz-Tendero, Sergio; Martín-Sómer, Ana; Gómez, Clarisa Villegas; Belmonte-Vázquez, José L.; Ramírez-Ornelas, Diana E.; Peña-Cabrera, Eduardo; Fraile, Alberto; Cruz, David Cruz; Alemán, José
Abstract : BODIPY as an EWG in asymmetric catalysis is presented. Abstract : In this work we have found that a BODIPY can be used as an electron withdrawing group for the activation of double bonds in asymmetric catalysis. The synthesis of cyclohexyl derivatives containing a BODIPY unit can easily be achieved via trienamine catalysis. This allows a new different asymmetric synthesis of BODIPY derivatives and opens the door to future transformation of this useful fluorophore. In addition, the Quantum Chemistry calculations and mechanistic studies provide insights into the role of BODIPY as an EWG.